1997
DOI: 10.1099/00207713-47-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Borrelia burgdorferi Sensu Stricto by Arbitrarily Primed PCR and Pulsed-Field Gel Electrophoresis

Abstract: Borrelia burgdorferi sensu lato is present all over the world. However, most species belonging to this complex have a limited distribution; the only exception is B. burgdorferi sensu stricto, which is encountered both in Europe and in the United States. The aim of this study was to clarify the way that B. burgdorferi sensu stricto migrated. To do this, we compared the genetic polymorphism of 33 B. burgdorferi sensu stricto strains isolated in Europe and 28 strains isolated in the United States by using both pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
6
30
0
Order By: Relevance
“…We observed greater genetic diversity among the 15 North American samples (mean genetic distance ϭ 0.46) than among 12 European samples (mean genetic distance ϭ 0.41). Perhaps because of a relatively small sample size, this trend is not statistically significant (t ϭ 0.009) but it is consistent with previous evolutionary models postulating a founder effect as North American B. burgdorferi sensu stricto moved to the Old World (15,23). However, diversity within B. burgdorferi sensu stricto could likewise be affected by lateral transfer of genetic material from other species.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We observed greater genetic diversity among the 15 North American samples (mean genetic distance ϭ 0.46) than among 12 European samples (mean genetic distance ϭ 0.41). Perhaps because of a relatively small sample size, this trend is not statistically significant (t ϭ 0.009) but it is consistent with previous evolutionary models postulating a founder effect as North American B. burgdorferi sensu stricto moved to the Old World (15,23). However, diversity within B. burgdorferi sensu stricto could likewise be affected by lateral transfer of genetic material from other species.…”
Section: Resultssupporting
confidence: 71%
“…Numerous molecular techniques have recently been used to characterize Borrelia species, including 16S rRNA gene sequence analysis, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, Western blot analysis, pulsed-field gel electrophoresis, plasmid fingerprinting, randomly amplified polymor-phic DNA analysis, restriction fragment length polymorphism analysis, fatty acid profile analysis, and serotyping (4,8,15,33). For a more thorough review of the molecular typing methods used for Borrelia characterization, see reference 36.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated substantial genotypic variability among B. burgdorferi isolates (23,39,40,77). Thus, the extent to which these two isolates are representative of all virulent and attenuated strains is unclear, although increased expression of BBA74 was observed in the two attenuated strains studied thus far (B356 and B331).…”
Section: Discussionmentioning
confidence: 99%
“…Previously described procedures were used for the preparation of high-molecular-weight genomic DNAs and for PFGE (4,9). Rare-cutting endonucleases SacII, BssHII, and MluI were used to differentiate isolates.…”
Section: Methodsmentioning
confidence: 99%